A ANALISIS KOMPENSASI DAN STRES KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA USAHA KECIL DI KECAMATAN PURWOKERTO SELATAN KABUPATEN BANYUMAS - Edi Sumantri; Irwan Susanto Susanto (Majalah Imiah Manajemen & Bisnis, 2021)
The very tight competition situation forces the company to manage all activities and employees so that it can compete with its competitors. The intention to leave the employees must be responded properly so that employee turnover can be controlled. Compensation variables and job stress are thought to affect the intention to leave. This study provides information on the effect of compensation and job stress on the intention to leave employees at small businesses in Purwokerto, Banyumas district. The hypotheses proposed in this study are: compensation and work stress partially and simultaneously have a significant effect on Turnover Intention; and Compensation has a more significant effect on Turnover Intention. The research results of the first and second hypotheses were accepted, while the third hypothesis was rejected.